A high-throughput energy-aware medium-access-control protocol for wireless sensor networks. (27th July 2006) - Nguyen, Christopher K.; Kumar, Anup
The paper proposes a throughput and energy-aware medium-access-control protocol for wireless sensor networks. This innovative approach aggressively eliminates the wasted energy while increasing the throughput. The proposed throughput and energy-aware medium-access-control protocol solves the energy inefficiency caused by idle listening and overhearing. Communication is handled using the built-in synchronisation. Mobility and scalability are supported by the history-independent establishment of communication. Simulation experiments have been performed to demonstrate the effectiveness of the proposed approach compared to some recently proposed energy-efficient protocols.